The study on the relationship of workplace flexibility and turnover intention and innovative work behavior: Based on meditating effect of work-growth balance, perceived organizational support and moderating effect of self-leadership - Chung, HyunSun; Yang, HyunChul; Park, DongGun (Korean Journal of Industrial and Organizational Psychology, 2013)
The purpose of the present study was to investigate the influence of workplace flexibility on turnover intention and innovative work behavior in workplace and the mediating roles of work-growth balance and perceived organizational support. In addition, this study examined the moderating effect of self-leadership in the relationship between workplace flexibility and work-growth balance and perceived organizational support. The results from 182 participants provided evidences that (a)workplace flexibility was positively related to the work-growth balance and perceived organizational support, (b) work-growth balance and perceived organizational support were negatively related to the turnover intention and positively related to the innovative work behavior, (c) work-growth balance and perceived organizational support mediated the relationship between workplace flexibility and turnover intention and innovative work behavior. The study revealed that self-leadership moderated the relationship between workplace flexibility and work-growth balance and perceived organizational support. Based on the results, implications of these findings, limitations and future study directions were discussed.